A Systematic Review of Definitions for Neurological Complications and Disease Progression in Patients Treated Surgically for Degenerative Cervical Myelopathy. Issue 18 (15th September 2019) - Tetreault, Lindsay; Lange, Stefan F.; Chotai, Silky; Kryshtalskyj, Michael T.; Martin, Allan R.; Ahuja, Christopher S.; Wilson, Jefferson R.; Davies, Benjamin M.; Nouri, Aria; Devin, Clinton; Fehlings, Michael G.
Abstract : Study Design: Systematic review. Objective: This review aims to (1) outline how neurological complications and disease progression are defined in the literature and (2) evaluate the quality of definitions using a novel four-point rating system. Summary of Background Data: Degenerative cervical myelopathy (DCM) is a progressive, degenerative spine disease that is often treated surgically. Although uncommon, surgical decompression can be associated with neurological complications, such as C5 nerve root palsy, perioperative worsening of myelopathy, and longer-term deterioration. Unfortunately, important questions surrounding these complications cannot be fully addressed due to the heterogeneity in definitions used across studies. Given this variability, there is a pressing need to develop guidelines for the reporting of surgical complications in order to accurately evaluate the safety of surgical procedures. Methods: An electronic database search was conducted in MEDLINE, MEDLINE in Process, EMBASE and Cochrane Central Register of Controlled Trials for studies that reported on complications related to DCM surgery and included at least 10 surgically treated patients. Data extracted included study design, surgical details, as well as definitions and rates of surgical complications. A four-point rating scale was developed to assess definition quality for each complication. Results: Our search yielded 2673 unique citations, 42 of which met eligibility criteria and were summarized in this review. Defined complications included neurological deterioration, late onset deterioration, perioperative worsening of myelopathy, C5 palsy, nerve root or upper limb palsy or radiculopathy, surgery failure, inadequate decompression and progression of ossified lesions. Reported rates of these complications varied substantially, especially those for neurological deterioration (0.2%–33.3%) and progression of ossified lesions (0.0%–86.7%). Conclusion: Reported incidences of various complications vary widely in DCM surgery, especially for neurological deterioration and progression of ossified lesions. This summary serves as a first step for standardizing definitions and developing guidelines for accurately reporting surgical complications. Level of Evidence: 2 Abstract : Surgical decompression for degenerative cervical myelopathy can improve functional impairment, disability, and quality of life. Surgery, however, is associated with complications, including C5 palsy, new radiculopathy, and intraoperative spinal cord injury. There is a pressing need to develop standardized definitions of these complications in order to accurately evaluate surgical safety.